The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2020je006500
|View full text |Cite
|
Sign up to set email alerts
|

Martian Oxygen and Hydrogen Upper Atmospheres Responding to Solar and Dust Storm Drivers: Hisaki Space Telescope Observations

Abstract: Although Mars today possesses a thin atmosphere and a dry environment, many geological features on Mars suggest that the planet used to possess a thick atmosphere and water on the surface. One widely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…However, many observations have demonstrated that hydrogen escape rates from the Martian upper atmosphere vary seasonally due to seasonal change in vertical water vapor distribution [3][4][5][6][7] . Additionally, recent observations revealed that major dust storms, which expand regionally or globally on Mars, directly transfer water vapor from the lower to the upper atmosphere and rapidly change the vertical water distribution, increasing hydrogen escape [5][6][7][8][9][10][11][12][13] . Because major regional dust storms occur seasonally and global dust storms occasionally on Mars, monitoring Mars' hydrogen upper atmosphere and dust storms is crucial for understanding its water escape mechanisms.…”
mentioning
confidence: 99%
“…However, many observations have demonstrated that hydrogen escape rates from the Martian upper atmosphere vary seasonally due to seasonal change in vertical water vapor distribution [3][4][5][6][7] . Additionally, recent observations revealed that major dust storms, which expand regionally or globally on Mars, directly transfer water vapor from the lower to the upper atmosphere and rapidly change the vertical water distribution, increasing hydrogen escape [5][6][7][8][9][10][11][12][13] . Because major regional dust storms occur seasonally and global dust storms occasionally on Mars, monitoring Mars' hydrogen upper atmosphere and dust storms is crucial for understanding its water escape mechanisms.…”
mentioning
confidence: 99%
“…So, we can clarify the connection between the outflow of ions and the atmospheric events in the lower atmosphere such as dust storms and water ice clouds. Recent observations by Mars orbiters and space telescopes have revealed the importance of high-altitude water for hydrogen escape to space (e.g., Clarke et al 2014;Chaffin et al 2017;Heavens et al 2018;Aoki et al 2019;Stone et al 2020;Masunaga et al 2020). It has also been suggested that the oxygen loss rate may decrease during a dust storm (Lee et al 2020).…”
Section: Atmospheric Escapementioning
confidence: 99%
“…(2014) who found for their orbit 5,070 that an assumed exobase temperature of 180 K gave n H = 1.4 × 10 5 cm −3 ; Halekas (2017), who found n H ∼ 3 × 10 5 cm −3 for an assumed exobase temperature of 200 K; and Qin (2021), who found temperatures near 200 K and H densities near 8 × 10 4 cm −3 . Other recent studies of H and O in the thermosphere either did not report retrievals or had no data covering northern spring equinox (Bhattacharyya et al., 2015; Chaffin et al., 2018; Chaufray et al., 2008, 2015; Feldman et al., 2011; Masunaga et al., 2020; Qin, 2020). Importantly, we require no modification to the instrument calibration or solar flux to obtain a good model/data match.…”
Section: Model Description and Data Comparisonmentioning
confidence: 99%
“…Hopkins Ultraviolet Telescope (HUT) (Feldman et al, 2000) and Far Ultraviolet Spectroscopic Explorer (Krasnopolsky & Feldman, 2002), with more recent Hisaki measurements giving spatial resolution comparable to the size of the disk (Masunaga et al, 2020). The only spacecraft flyby observation was made by Rosetta/Alice (Feldman et al, 2011), and only the optically thin H coronal 102.6 nm emission far from the disk was analyzed.…”
mentioning
confidence: 99%